Reconfigurable and versatile augmented reality optical setup for tangible experimentations - Bruno Bousquet; Martin Hachet; Vincent Casamayou; Erwan Normand; Jean-Paul Guillet; Lionel Canioni (Springer, 2024)
Abstract HOBIT, which stands for "Hybrid Optical Bench for Innovative Teaching and learning" is an educational platform that leverages the combination of numerical simulation and physical manipulation to facilitate learning of complex phenomena and motivate users about wave optics in practical work. HOBIT operates in real time and is self-adaptive, providing realistic displays of optical phenomena with virtual augmentations designed to facilitate their understanding. HOBIT makes it quick and easy to build any reconfigurable optical experiment. Students can manipulate optical components and observe the changes induced on detectors and displays. We detail the technology, the simulation model and the initial teaching aids. Current and future enhancements should meet the needs of students at different levels, from high school to higher education degrees.